1984
DOI: 10.3109/00016348409155552
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Menarcheal Age From 1966 to 1983 in Denmark

Abstract: Mean age at menarche was estimated by the status quo method in the same region of Denmark in 1965-66 and 1982-83 in 983 and 1 591 girls, respectively. During that period menarcheal age decreased by 4 months from 13.40 to 13.03 years, subsequent to a similar decrease from 1949-50 (2) to 1965-66. Comparison with recent data from the other Nordic countries, except Norway, indicates that age at menarche is now close to 13 years, and a halt in the trend towards earlier menarche is not evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
2
12
0
1
Order By: Relevance
“…In Denmark, the mean menarcheal age has declined from approximately 17 years in the 19 th century to approximately 13–13.5 years [18]. In studies of birth cohorts from the same period, as described in the present study, age at menarche declined from 13.8 years to 13.0 years [19], [20], which is supported by our finding of a declining age at puberty in girls born between 1930 and 1969. Interestingly, the tendency towards earlier sexual maturation in Denmark seemed to cease in studies performed after the present study [21][23].…”
Section: Discussionsupporting
confidence: 89%
“…In Denmark, the mean menarcheal age has declined from approximately 17 years in the 19 th century to approximately 13–13.5 years [18]. In studies of birth cohorts from the same period, as described in the present study, age at menarche declined from 13.8 years to 13.0 years [19], [20], which is supported by our finding of a declining age at puberty in girls born between 1930 and 1969. Interestingly, the tendency towards earlier sexual maturation in Denmark seemed to cease in studies performed after the present study [21][23].…”
Section: Discussionsupporting
confidence: 89%
“…For example, in Denmark, the average AOM declined by 4 months from 13.40 to 13.03 years between 1965/ 1966 and 1982/1983, a 2.4 months drop in AOM per decade was reported in Brazil among a cohort of women born between 1931 and 1977, and in the USA an average drop in AOM by 2.5 months was observed between 1963-1970 and 1988-1994 with a further decline by 2.3 months in (Helm and Helm, 1984Anderson et al, 2003;Do Lago et al, 2003;Anderson and Must, 2005). Although the decline in timing of menarche over the past century was mainly attributed to improved socioeconomic status (SES), as reflected by better sanitation and nutrition, the ongoing declining secular trend in many developed countries suggests that causes other than socioeconomic changes must also exist (Zacharias and Wurtman, 1969;Marrodan et al, 2000;Danubio et al, 2004;Anderson and Must, 2005;Aksglaede et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Since AOM has notably declined over time worldwide (Helm and Helm, 1984;Adadevoh et al, 1989;Papadimitriou et al 1999;Olesen et al, 2000;Anderson et al, 2003;Do Lago et al, 2003;Silva and Padez, 2006)-much more than genetic factors alone can explain-this decrease must presumably have, at least in part, environmental causes. For example, in Denmark, the average AOM declined by 4 months from 13.40 to 13.03 years between 1965/ 1966 and 1982/1983, a 2.4 months drop in AOM per decade was reported in Brazil among a cohort of women born between 1931 and 1977, and in the USA an average drop in AOM by 2.5 months was observed between 1963-1970 and 1988-1994 with a further decline by 2.3 months in (Helm and Helm, 1984Anderson et al, 2003;Do Lago et al, 2003;Anderson and Must, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Only small declines in AAM were reported after the 1960s in developed countries such as Denmark [9], the Netherlands [10], the UK [11], Germany [12], Japan [13] and Spain [14]. However, a large cross-sectional study from the USA published in 1997 challenged the belief that the decline in the age of pubertal milestones had reached a plateau, and revealed that the important milestones in pubertal development seem to be occurring at an earlier age in recent decades [15].…”
Section: Introductionmentioning
confidence: 99%